(Re)assembling the ‘normal’ in neoliberal policy discourses: tracing gender regimes in the age of risk - Katarina Giritli Nygren; Siv Fahlgren; Anders Johansson (Nordic Journal of Social Research)
The purpose of this article is to explore through a reading of an official Swedish policy document what questions and challenges such a document poses for feminist theory by the way the ‘normal’ is (re)assembled in accordance with what others have called the risk politics of advanced liberalism.  The intensified focus on risk in neoliberalism has seen responsibility move from the state to individuals, and old divisions between society and market as well as between civil society and state are being refigured. The argument put forward here is that current modes of governance tend to neglect the complexities of present-day life courses when using a gender-‘neutral’ approach to social policy that is in fact the work of a gender regime.